Antimutagenic activity of Carica papaya L. assayed in vivo by micronucleus test - I.C. Kalil; B.A.V. Gibson; C.A. Ribeiro; L.S. Benincá; G.A. Brasil; T.U. Andrade; M.C.P. Batitucci; D.C. Endringer (São Paulo State University (UNESP), 2019)
There is little information about in vivo toxic effects of the ethanolic extract of leaves of Carica papaya L. (ECP). Therefore, in this study ECP was characterized chemically by HPLC-RP and the antimutagenic and cytotoxic activities of an aqueous solution of ECP (CA) were assessed by the micronucleus (MN) bioassay. The extract consisted mainly of polar substances, one of which was rutin. The MN test was performed on groups of Wistar rats, as follows: negative control (NC) - vehicle; positive control (CP40) - cyclophosphamide (40 mg/kg, ip), 24h; extract-treated (CA) - ECP (500 mg/kg, po), 24h; extract + cyclophosphamide-treated (CACP40) - ECP (500 mg/kg, po), 48, 36 and 24 h, plus cyclophosphamide (40 mg/kg, ip), 24h. The MN index was 3.2 ± 1.79 and 1.6 ± 0.5, for NC and CA, and the PCE-to-NCE ratio was 1.38 ± 0.52 and 1.13 ± 0.28, respectively, indicating low cytotoxicity of CA. CP40 showed a high MN index of 20 ± 4.9, but CACP40 only 3.0 ± 1.6, the same as NC, indicating an antimutagenic effect. The study suggests that ECP has low toxicity and possesses an antimutagenic protective effect in which rutin may be involved.